Efek Pemberian Eucheuma spinosum sebagai Profilaksis dalam Penghambatan Peningkatan SGPT pada Tikus yang Diinduksi Dexamethasone - HANDAJANI, FITRI; PERMANA, I GEDE PUTU BAYU TIRTA; TARUNA, DODY; UNTARI, NI KOMANG SRI DEWI (Hang Tuah Medical Journal, 2023)
Serum Glutamic Pyruvate Transaminase (SGPT) is a specific biomarker for detecting liver disease. This study aimed to determine the effect of giving 200 mg/Kg BW of Euchema spinosum extract as a prophylaxis against increasing SGPT in Rattus norvegicus rats injected with dexamethasone 8mg/Kg BW for six days. This experimental study with a randomized posttest-only control group design using 24 white male rats which were divided into three groups; group 1 was the untreated group, group 2 was given dexamethasone 8 mg/Kg BW for six days, the group 3 was given prophylactic 200 mg/Kg BW Eucheuma sp. extract for 13 days. After the treatment period, the group was terminated, and SGPT levels were measured using Cobas Integra. SGPT levels were then analyzed using SPSS. The normality test results for SGPT levels obtained a value of p> 0.05, and this value was only obtained from group 1 (p = 0.085) and group 2 (p = 0.224), while the group 3 showed that the distribution of data was not normally distributed (p = 0.022). The Kruskal-Wallis test showed a mean difference in SGPT levels between groups. The Mann-Whitney U test obtained a lower SGPT score in group 3 than in group 2 (p=0.007). Group 1, compared to group 3, decreased (p=0.001). Giving extract of Eucheuma sp. at a dose of 200 mg/Kg BW can inhibit the increase in SGPT levels in dexamethasone-induced white male rats (Rattus norvegicus).